2019
DOI: 10.1002/anie.201814660
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylation with Carbon Monoxide: The Direct Conversion of Carboxylic Acids into Potent Acid Triflate Electrophiles

Abstract: We report a new strategy for the conversion of carboxylic acids into potent acid triflate electrophiles. The reaction involves oxidative carbonylation of carboxylic acids with I2 in the presence of AgOTf, and is postulated to proceed via acyl hypoiodites that react with CO to form acid triflates. Coupling this chemistry with subsequent trapping with arenes offers a mild, room temperature approach to generate ketones directly from broadly available carboxylic acids without the use of corrosive and reactive Lewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…[ 4 ] Typically, high purity CO from CO 2 hydrogenation via reverse water gas shift (RWGS) reaction could be used as raw material for the Fischer–Tropsch synthesis. [ 5 ] producing carbonyl‐containing compounds, [ 6 ] acetamides, [ 7 ] triflate electrophiles, [ 8 ] and purifying nickel in Mond process. [ 9 ] In this way, photothermal catalytic CO 2 reduction technology can significantly reduce energy consumption and seems promising for carbon recycle, but the fabrication of high‐quality catalyst is not yet mature.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Typically, high purity CO from CO 2 hydrogenation via reverse water gas shift (RWGS) reaction could be used as raw material for the Fischer–Tropsch synthesis. [ 5 ] producing carbonyl‐containing compounds, [ 6 ] acetamides, [ 7 ] triflate electrophiles, [ 8 ] and purifying nickel in Mond process. [ 9 ] In this way, photothermal catalytic CO 2 reduction technology can significantly reduce energy consumption and seems promising for carbon recycle, but the fabrication of high‐quality catalyst is not yet mature.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic data matched those reported in literature. 18 This article is protected by copyright. All rights reserved.…”
Section: -(Methylsulfonyl)benzonitrile (8)mentioning
confidence: 99%
“…19 A decarboxylative approach for the acylation of (hetero)arenes has been disclosed by Kinney and Arndtsen via direct conversion of carboxylic acids into acid triflate electrophiles using a synergy of CO, I 2 , and AgOTf. 20 In a seminal experiment in 2021, Chen and co-workers reported the acylation of azoles with carboxylic acids in the presence of various bulky phosphine ligands through the Pd/Cu cooperative catalysis. 21 During the same time, a photoredox acylation approach for the synthesis of γ-oxo-α-amino acid derivatives has also been reported which employed photoredox catalysis in combination with triphenylphosphine to generate acyl radicals from the readily available (hetero)aromatic and vinylic carboxylic acids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Later, Fu et al reported a different strategy for the acylation of 2-phenylpyridines with aromatic acids using Pd­(OAc) 2 as the catalyst, and trifluoroacetic anhydride as the activating agent of the acids . A decarboxylative approach for the acylation of (hetero)­arenes has been disclosed by Kinney and Arndtsen via direct conversion of carboxylic acids into acid triflate electrophiles using a synergy of CO, I 2 , and AgOTf . In a seminal experiment in 2021, Chen and co-workers reported the acylation of azoles with carboxylic acids in the presence of various bulky phosphine ligands through the Pd/Cu cooperative catalysis .…”
Section: Introductionmentioning
confidence: 99%